Management of Acute Kidney Injury in Extremely Low Birth Weight Infants - Branagan, Aoife; Costigan, Caoimhe S.; Stack, Maria; Slagle, Cara; Molloy, Eleanor J. (Frontiers in Pediatrics, 2022)
Acute kidney injury (AKI) is a common problem in the neonatal intensive care unit (NICU). Neonates born at < 1000 grams (extremely low birth weight, ELBW) are at increased risk secondary associated comorbidities such as intrauterine growth restriction, prematurity, volume restriction, ischaemic injury, among others. Studies estimate up to 50% ELBW infants experience at least one episode of AKI during their NICU stay. Although no curative treatment for AKI currently exists, recognition is vital to reduce potential ongoing injury and mitigate long-term consequences of AKI. However, the definition of AKI is imperfect in this population and presents clinical challenges to correct identification, thus contributing to under recognition and reporting. Additionally, the absence of guidelines for the management of AKI in ELBW infants has led to variations in practice. This review summarizes AKI in the ELBW infant and includes suggestions such as close observation of daily fluid balance, review of medications to reduce nephrotoxic exposure, management of electrolytes, maximizing nutrition, and the use of diuretics and/or dialysis when appropriate.